Beyond averages: Situational lesson to lesson level interplay between relatedness and competence - Koivuhovi, Satu; Malmberg, Lars-Erik; Rawlings, Anna Maria; Salonen, Reito Visajaani; Hotulainen, Risto (Elsevier, 2026)
Although relatedness and competence are central psychological needs for students' motivation and well-being, their moment-to-moment variation in classrooms remains underexplored. This study examined fluctuations in adolescents' experiences of relatedness and competence across a school week using intensive longitudinal data from 118 secondary school students (average of 21 responses per student). Multilevel dynamic structural equation models showed that most variance was situational, with 30–40% reflecting stable between-person differences. Subject-specific patterns emerged, as experiences differed across school subjects. Prior relatedness predicted both subsequent relatedness and competence, suggesting that social connection can foster academic confidence. Conversely, prior competence slightly reduced later relatedness satisfaction and increased relatedness frustration, indicating a potential trade-off with social engagement. Additionally, the number of peers per lesson predicted greater relatedness satisfaction and lower frustration. These findings underscore the value of capturing motivational dynamics at the situational level and tailoring support to both academic and social needs.